EFEKTIVITAS BANTUAN LANGSUNG TUNAI (BLT) DANA DESA PADA MASYARAKAT MISKIN TERDAMPAK PANDEMI COVID-19 DI DESA PENYASAWAN KECAMATAN KAMPAR KABUPATEN KAMPAR TAHUN 2020 - M. Sherfi Pahlevi; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The effectiveness of Direct Cash Assistance (BLT) during the covid-19 pandemic is the government's effort to improve the people’s economy and increase people’s competitiveness during the covid-19 pandemic in Indonesia. The problem in this study is that there are still people who should get direct cash assistance, but do not get it, so there is a gap that occurs in the village of Penyasawan. The mechanism for distributing BLT assistance has changed in terms of the index of assistance received by the people who receive it. The purpose of this study is to determine the effectiveness of direct cash assistance (BLT) carried out by the government to improve the community's economy during the COVID-19 pandemic, as well as to describe the mechanism of direct cash assistance (BLT) for village funds for poor communities affected by the COVID-19 pandemic. 19 in Penyasawan Village, Kampar District, Kampar Regency. The approach in this study is to use a qualitative approach and the type of research is descriptive. The location of the research was carried out in Penyasawan Village, Kampar District, Kampar Regency, using data collection techniques through interviews and documentation. The results showed that the effectiveness of Village Fund Cash Direct Assistance (BLT) for the poor affected by the COVID-19 pandemic in the Pengasawan Village, First, the mechanism carried out by the Penyasawan Village government in implementing direct cash assistance by collecting data on the community according to predetermined criteria and disbursement in accordance with the established mechanism. Second, the effectiveness of Cash Direct Assistance (BLT) implemented by the Penyasawan Village government has been running in accordance with applicable laws and has been in accordance with the relevant presidential and ministerial regulations. Keywords : Effectiveness. Mechanism Cash direct assistance (BLT)